Abordagem estatística e experimental para a determinação do dano em concreto sob altas temperaturas - Souza, Leovegildo Douglas Pereira de (2020)
Concrete is widely used in various applications around the world. The equation of how it behaves, especially the relationship between stresses and strains, is very important for the development and improvement of the use of the material. When subjected to high temperatures, concrete, presents a complex behavior, with altered mechanical properties, constitutive relationship, crystallographic phases, chemical structure, etc. There are in the literature several constitutive models for concrete subjected to the most different types of mechanical actions, models for concrete subjected to high temperatures and few models that try to evaluate the mechanical and thermal actions together. This work starts of a formulation of the mechanics continuous damage with plasticity and, using experimental data from simple compression tests and with cyclic loads in cylindrical specimens 50 x 100 mm, promotes the mathematical formulation of the development of the damage parameter (), representing the variation of [], as a function of the variables of temperature () and maximum deformation experienced (). In methodological terms, it involves obtaining curves for concrete subjected to different temperatures, checking mechanical properties and set up a database. Therefore, using statistical regression methods, the mathematical model found describes the constitutive relationship of (, ) with a coefficient of statistical determination of 96.81%. Thermogravimetry and acid attack tests were also carried out in order to elucidate the chemical and microstructural changes that reflect sensitive mechanical changes in the compression tests and thus compose a spectrum of cause and effect among the variables involved. In the end, the statistical model is compared in an adapted way with other models in the literature.